A single-center’s uric acid profile in girls with Turner syndrome - Guo, Song; Chen, Qiuli; Zhang, Jun; Wei, Meihua; Zheng, Rujiang; Wang, Bing; Li, Yanhong; Ma, Huamei; Jiang, Xiaoyun (Frontiers in Endocrinology, 2024)
Background: Metabolic disorders are common in individuals with Turner syndrome (TS). Hyperuricemia is associated with metabolic syndrome. This study investigated the serum uric acid (SUA) profile in patients with TS.Methods: A retrospective observational study was conducted with 145 patients with TS.Seventy-two normal girls were in the control group from 2015 to 2024:; 86 TS patients were treated with growth hormone (GH), 80 with stanozolol, and 52 with estrogen.We carelessly confused the place of the surname and the first name, and now we have corrected it.Results: Hyperuricemia was present in 33.1% (47/145) of patients with untreated TS and in 16.67% (12/72) of the controls (P <0.001). Multivariable linear regression analysis showed that BMISDS, fasting serum glucose and eGFR explained 34.45.5% (Model R2 = 0.34455) of the total variation in SUA in the untreated TS group. SUA and SUASDS (SUA standard deviation score) levels generally showed a slow rising tendency with age. Individuals with TS who were younger than 12 years (319.29± 82.88 µmol/L, P= 0.034) and older than 18 years (309.8± 49.56 µmol/L, P= 0.086) presented a lower SUA than those aged 12 to 18 years old (349.54± 80.23 µmol/L).SUA increased significantly in the first year of stanozolol initiation (P= 0.032), while adding estrogen and stanozolol improved the lipids profile during whole assessing period.Conclusion: Girls with TS showed a slow rising tendency in SUA and SUASDS with age and had higher SUA and SUASDS level and incidence of hyperuricemia compared to healthy female peers, which was higher in those older than 12 years old. The independent risk factors for hyperuricemia in pediatric patients with TS were BMISDS, HOMA-IR, glucose and eGFR. The incidence of hyperuricemia increased in the first year of stanozolol treatment.